Impact of 3D printing on vascular surgery training and preoperative planning - Haris Vukas; Samra Kadić-Vukas; Sumeja Ćatić; Ruvejda Dizdarević; Farah Dedović; Nail Šehić; Merim Jusufbegović (Medicinski glasnik, 2026)
Aim: To investigate the impact of three-dimensional (3D) printing technology on vascular surgery, focusing on its role in preoperative planning and surgical training. Methods: A systematic review was conducted of studies published between 2017 and 2024 that evaluated 3D printing in vascular surgery. Databases searched included MEDLINE and CENTRAL. Eligible studies reported applications of 3D printing in preoperative planning, simulation, or surgical education. Results: Analysis of relevant studies revealed that 3D-printed vascular models improved surgical precision, reduced fluoroscopy time, enhanced technical skill acquisition, and increased trainees’ confidence. Models based on computed-tomography angiography data provided accurate, patient-specific anatomy for classic or endovascular aortic aneurysm repair and other vascular procedures. Conclusion: 3D printing significantly enhances vascular-surgery training and preoperative preparation by providing realistic, patient-specific simulations that improve both technical competence and surgical outcomes.
Keywords: Education; Medical; models; Simulation; Three-Dimensional; Training